The association of parental smoking and nutritional status with acute upper respiratory infection of children under five years of age in Manila, Philippines - Ly Penh Sun.
A case-control study was conducted to determine the association of parental smoking and nutritional status with acute upper respiratory infection. Studied subjects were 230 (115 cases and 115 controls) children, under five years of age in Manila who were patients of Out-Patient Department of Philippine General Hospital Data were collected using the interview of mothers or caretakers who participated in the study. Two-way frequency tabulation was used to assess association of parental smoking and nutritional status with actue upper respiratory infection. Logistic regerssion was used to summarize the association of parental smoking, nutritional status and acute upper respiratory infection controlling for confounders. The association between parental smoking and acute upper respiratory infection were found to be statistically significant. Children with AURI were 7.5 times more likely to have had high and moderate exposure and 3.7 times low exposure of parental smoking, compared to children without acute upper respiratory infection. The study failed to show the association of nutritional status with AURI. The results of this study showed that many cases of AURI of children may be prevented through a sustained effort to discourage smoking initiation and to encourage smoking cessation.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Respiratory infections; Smoking; Nutrition